Anatomic and operative predictors of aortic expansion following aortic dissection repair - Ryaan EL-Andari; Sabin Bozso; Yongzhe Hong; Michael Moon (Scientific Reports)
Abstract Following surgical repair of acute type A aortic dissection(ATAAD), distal aortic degeneration and growth may occur. Previous evidence has suggested that false lumen(FL) communications and flow may influence postoperative aortic remodeling, although the contribution of branch vessel dissection and FL communications is unclear. Patients who underwent ATAAD repair from 2017 to 2023 at a single center with at least 1 year of follow-up imaging were included in this study. Patients were grouped based on aortic pathology and surgical repair. Preoperative and postoperative measurements were taken at the level of zone 1 and between zones 4/5. 63 patients were included in this study. 87.3% received a hemiarch repair, 34.9% received hemiarch + AMDS Hybrid prosthesis, and 12.7% received a total arch replacement. Proximal aortic remodeling was not reliably predicted by the presence of FL communications or surgical approach. Distal aortic growth was independently associated with ≥ 3 or 4 visceral vessel dissections(p = 0.04 − 0.005). In conclusion, distal aortic remodeling following ATAAD repair was predicted by visceral vessel involvement. While the aortic arch is often emphasized at the time of ATAAD repair, features of the distal aorta may help to risk stratify patients for long-term adverse events, helping to guide initial management and post-ATAAD repair follow-up.